ЗНАХІДКА ГЛАДКОГО РОМБА SCOPHTHALMUS RHOMBUS (L., 1758) (PLEURONECTIFORMES: SCOPHTHALMIDAE) У ПРИБЕРЕЖНИХ ВОДАХ КРИМУ - Гирагосов, В. Е.; Ханайченко, А. Н.; Кирин, М. П.; Гуцал, Д. К. (Marine Ecological Journal, 2023)
Record of the brill Scophthalmus rhombus (L., 1758) (Pleuronectiformes: Scophthalmidae) in the coastal waters of Crimea.